The Effect of Therapeutic Communication on The Anxiety Level of Preoperative Patients at RSUD Jendral Ahmad Yani Metro City - Al'arif, Afrizal; Agustriyani, Feri (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: The purpose of this study was to determine this study to analyze the application of therapeutic communication to the anxiety level of preoperative patients at RSUD Jendral Ahmad Yani Metro City. Method: The research method is obtained from the results of interviews with clients and observations of the client's condition during the assessment process and written in the form of notes then copied in the form of nursing care, an activity plan carried out for three days with the application of therapeutic communication in preoperative patients with anxiety level problems at Jendral Ahmad Yani Metro City Hospital. Result: The results of the evaluation of priority nursing diagnoses, namely anxiety related to situational crises, showed a decrease in anxiety levels and the patient looked calmer than before and after the application of therapeutic communication. Conclusion: Based on these results the author concluded that the problem of anxiety was resolved.